Interventions to Challenge Auditory Hallucinations Through Strengthening Coping and Motivation in Patients with Schizophrenia: Case Report - Sari, Lia; Sriati, Aat (Universitas Malahayati, 2023)
ABSTRACT Interventions for hallucination patients include recognizing hallucinations, and teaching patients to challenge hallucinations. Factors that influence the client's ability to control hallucinations are the client's response attitude towards hallucinations. The generalist interventions of shaming are done with coping strengthening and motivation as a therapy to change maladaptive thoughts and focus the mind. This case report aims to evaluate coping strategies and motivational reinforcement in an intervention to control auditory hallucinations. This paper was written using the case report method of scientific monitoring days in nursing care. A 15-year-old female client was admitted to the psychiatric hospital with complaints of talking to herself and attempted suicide by cutting her wrist veins. The client did not complain of physical problems. Based on the results of the assessment, the client appeared to be daydreaming and talking to herself. Clients are given generalist therapy to block hallucinations to strengthen motivation and coping. Motivational and coping strengthening was carried out by encouraging the client to convince himself that the hallucinations he heard were not real and encouraging the client to change his beliefs and thoughts to something positive such as the client's ability. This intervention focuses the mind to focus on the real thing around the client and convinces the self to ignore the hallucinatory sound by